Integrating behavioral, social, and technological factors in cryptocurrency investment decisions - Tang My Sang (PLoS ONE, 2026)
Cryptocurrency markets are characterized by high volatility and behavioral biases. Although several studies have examined psychological, social, and technological factors separately, few have comprehensively integrated them within a unified framework based on behavioral finance. This study addresses this gap by examining the interplay among digital financial literacy, impulsivity, social media financial influencers, fintech self-efficacy, and attitude toward investment in shaping investment decisions in Vietnam’s cryptocurrency market. Data were collected from 505 individual investors, and partial least squares structural equation modeling was employed to test the proposed framework. The results indicate that digital financial literacy fosters positive attitudes toward investment and directly supports informed investment decision-making. However, contrary to conventional expectations, digital financial literacy is positively associated with impulsivity-related investment behavior, suggesting that higher perceived digital competence may foster overconfidence and an illusion of control in highly volatile cryptocurrency markets. Social media financial influencers significantly shape investors’ attitudes and also exert a direct influence on investment decisions, highlighting both attitudinal and behavioral pathways. Furthermore, fintech self-efficacy moderates the relationship between attitudes and investment decisions by reducing investors’ reliance on attitudinal cues when making investment choices. The findings highlight the importance of distinguishing rapid informed decision-making from affect-driven impulsivity and emphasize the role of overconfidence and perceived digital literacy in shaping investor behavior. Practically, the results call for targeted digital financial education and regulatory oversight of online financial content to promote informed and sustainable investment practices.